THE INFLUENCE OF JOB SATISFACTION, ORGANIZATIONAL COMMITMENT, AND ORGANIZATIONAL CULTURE ON ORGANIZATIONAL CITIZENSHIP BEHAVIOR AMONG EMPLOYEES OF SKPK EAST ACEH. - Rahma Tina; Likdanawati; Julimursyida; Maisyura; Henny Irawati (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2024)
This study aims to investigate the impact of Job Satisfaction, Organizational Commitment, and Organizational Culture on Organizational Citizenship Behavior among employees of SKPK East Aceh. The independent variables include Job Satisfaction, Organizational Commitment, and Organizational Culture, while the dependent variable is Organizational Citizenship Behavior. The research adopts a quantitative approach, gathering data through a questionnaire consisting of questions and statements distributed to the employees of SKPK East Aceh. Data is scored using a Likert scale. The study was carried out at two SKPKs in East Aceh, specifically the East Aceh DPRK with 39 respondents and the East Aceh Inspectorate with 50 respondents, using a saturated sample approach where all populations were included, resulting in a total of 89 respondents. Multiple linear regression analysis was conducted using the SPSS (Statistical Program for Social Science) program. The findings indicate that Job Satisfaction and Organizational Commitment do not have a significant influence on Organizational Citizenship Behavior among Employees of SKPK East Aceh, whereas Organizational Culture does influence Organizational Citizenship Behavior among Employees of SKPK East Aceh. Higher levels of Job Satisfaction and Organizational Commitment within a government institution are associated with increased Organizational Citizenship Behavior or extra-role behavior among employees, ultimately leading to improved employee performance.